EFFECT OF MUTAGENESIS ON GROWTH AND YIELD RELATED TRAITS IN BLACKGRAM (Vigna mungo (L.) Hepper) - M. SREEVALLI DEVI *, D. MOHAN REDDY, V.L.N. REDDY, D. LOKANADHA REDDY, P. SUDHAKAR and S. SOFIA, (The Journal of Research ANGRAU, 2021)
The investigation was conducted to understand the immediate effect of mutagenesis on growthand yield traits in blackgram in order to select most effective mutagen and its dose/concentrationwhich induce desired improvement without disturbing the better attributes. The seeds of two varietiesof blackgram viz., LBG 752 and TBG 104 were treated with gamma rays (200 Gy, 300 Gy, 400 Gy,500Gy and 600 Gy), EMS (Ethyl Methane Sulphonate) (0.2%, 0.3%, 0.4%, 0.5% and 0.6%) and MH(Maleic Hydrazide) (0.01%, 0.02% and 0.03%). The observations were recorded on seed germination,shoot length and root length under in-vitro condition and seedling emergence, seedling survival,seedling height, pollen fertility, plant height, number of primary branches per plant, number of clustersper plant, number of pods per plant, number of seeds per pod, pod length, seed fertility, 100-seedweight and seed yield per plant under field condition. Higher doses of all the mutagens causedconsiderable reduction in all the traits studied. MH treatment resulted in drastic reduction in seedlingcharacters viz., seedling emergence, seedling survival and seedling height followed by EMS andgamma rays treatment. Based upon the sensitivity of mutagen, gamma rays were highly effective formodifying majority of the traits in the crop with less biological damage followed by EMS and MHtreatments. Both the parental varieties differed themselves for mutagen treatments. The reduction inthe traits with increasing dose of mutagens was more prominent in LBG 752 than TBG 104 indicatedthat LBG 752 was more sensitive to mutagen treatment. These findings would greatly help for costeffective selection of mutagen and variety for successful generation of variation in mutation breedingprogrammes aimed at blackgram crop improvement.